THE EFFECT OF FILLER ON MORPHOLOGY AND ELEMENTS BIOCOMPOSITE PCL/PLLA/NHA - Salsah, Rizka Putri; Purniawan, Agung; Sutarsis, Sutarsis (INFOKUM, 2022)
Implants are internal fixators that are implanted into the human body. Implantable materials that have biodegradable properties in recent years. This research aims to make a matrixed biocomposite of a mixture of polycaprolactone (PCL) and poly(l-lactic acid (PLLA) with a modified nano hydroxyapatite (nHA) filler of one of the silane coupling agents, namely 3-aminopropyltriethoxysilane (APTES) and analyze the effect of the addition of PLLA and nHA on morphology and elements. PCL was chosen as a matrix because it has biodegradable, ductile and low degradation rate properties and is mixed with PLLA because it has high biodegradable and mechanical properties but a high degradation rate. So, combining PCL and PLLA can make the mechanical properties of the polymer more optimized and promising for use in bone fixation devices. nHA was chosen because it has bone-like properties and has excellent biocompatibility. The variations used are PCl/PLLA composition ratios of 70:30, 80:20, 90:10 and the addition of nHA modified by APTES with variations of 10, 20, and 30%. The results of the SEM analysis show that with the addition of the percentage of PLLA and nHA 20% get optimal results. EDX results validate the elements or elements contained in the PCL/PLLA/nHA biocomposite.